A New Anthology of American Song 25 songs - NATIVE (G. Schirmer. Inc., 1942)
Barber, Samuel . . . The Daisies. Op. 2, No. 1nBeach, Mas H.H.A Meadow-Larks. Op. 79, No. 1nCadman, Charles Wakerfield A Moonlight song op. 42. No. 2nCambell-Tipton The Cryng of Water (Le Cri des Eaux)nCarpenter, John Alden Looking-Glass River ...